Assessing Free-Radical-Mediated DNA Damage during Cardiac Surgery: 8-Oxo-7, 8-dihydro-2′-deoxyguanosine as a Putative Biomarker. (4th June 2017) - Turnu, Linda; Di Minno, Alessandro; Porro, Benedetta; Squellerio, Isabella; Bonomi, Alice; Manega, Chiara Maria; Werba, José Pablo; Parolari, Alessandro; Tremoli, Elena; Cavalca, Viviana
Abstract : Coronary artery bypass grafting (CABG), one of the most common cardiac surgical procedures, is characterized by a burst of oxidative stress. 8-Oxo-7, 8-dihydro-2′-deoxyguanosine (8-oxodG), produced following DNA repairing, is used as an indicator of oxidative DNA damage in humans. The effect of CABG on oxidative-induced DNA damage, evaluated through the measurement of urinary 8-oxodG by a developed and validated liquid chromatography-tandem mass spectrometry (LC-MS/MS) method in 52 coronary artery disease (CAD) patients, was assessed before (T0), five days (T1), and six months (T2) after CABG procedure. These results were compared with those obtained in 40 subjects with cardiovascular risk factors and without overt cardiovascular disease (CTR). Baseline (T0) 8-oxodG was higher in CAD than in CTR (p = 0.035 ). A significant burst was detected at T1 (p = 0.019 ), while at T2, 8-oxodG levels were significantly lower than those measured at T0 (p < 0.0001 ) and comparable to those found in CTR (p = 0.73 ). A similar trend was observed for urinary 8-iso-prostaglandin F2 α (8-isoPGF2 α ), a reliable marker of oxidative stress. In the whole population baseline, 8-oxodG significantly correlated with 8-isoPGF2 α levels (r = 0.323, p = 0.002 ). These data argue for CABG procedure in CAD patients as inducing a short-term increase in oxidative DNA damage, as revealed by 8-oxodG concentrations, and a long-term return of such metabolite toward physiological levels.